Peranan dan Fungsi Polda NAD di Bidang Kamtibmas dalam Kerangka Otonomi Khusus di Provinsi Aceh - M. Gaussyah M. Gaussyah (Universitas Syiah Kuala, 2010)
ABSTRACT: This article aims to explain the role and function of NAD regional police in the law and order function in the specific autonomy in Aceh Province. NAD regional police not only responsible in the national law enforcement, but also responsible in the islamin law enforcement (Islamic Law) as a implementation specific autonomy consequency in Aceh Province. The unclear regulation about the role and function of NAD regional police in the law and order caused the implementation of law and order based on Islamic law still minimize in Aceh. (The Role and Function of NAD Regional Police in the Law and Order in the Specific Autonomy in Aceh Province)